2011
DOI: 10.1007/s12200-011-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Design of integrated-electrode tool for electrorheological finishing of optical glasses

Abstract: Electrorheological (ER) finishing utilizes the flow of electrically stiffened abrasive fluid through a preset converging gap formed by the work-piece surface and a moving tool. An ER finishing tool characterized by cathode integrated with anode together is proposed, whose electric field distribution is finite-element-analyzed (FEA) and is useful to finish both conductive work-piece and non-conductive ones. Experiments were performed to finish a K9 glass by this tool. After 30 minutes polishing, the surface rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…used ER polishing to polish tungsten carbide and invented an integrated tool for a five-axis ER polishing tool. , Lu et al studied the ER polishing properties of a tiny grinding wheel . Chen, et al designed an integrated electrode tool for ER polishing of optical glasses . Zhao et al studied the combined process of micro-EDM and ER polishing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…used ER polishing to polish tungsten carbide and invented an integrated tool for a five-axis ER polishing tool. , Lu et al studied the ER polishing properties of a tiny grinding wheel . Chen, et al designed an integrated electrode tool for ER polishing of optical glasses . Zhao et al studied the combined process of micro-EDM and ER polishing .…”
Section: Introductionmentioning
confidence: 99%
“…17 Chen, et al designed an integrated electrode tool for ER polishing of optical glasses. 18 Zhao et al studied the combined process of micro-EDM and ER polishing. 19 Su et al fabricated a wheel-like ER polishing tool to polish small parts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a result, electric field strength changes which leads to the possibility of unstable and non-uniform material removal. 77…”
Section: Precision Finishing Techniques Used For Fabrication Of Opticmentioning
confidence: 99%
“…To overcome this limitation, an advanced ER tool by incorporating cathode and anode together was developed by Chen et al 77 The schematic diagram of this tool is shown in Figure 14. The tool tip diameter is maintained within 1 mm and the edge of the tool must be round-shaped to avoid electric charge concentration at the edge.…”
Section: Precision Finishing Techniques Used For Fabrication Of Opticmentioning
confidence: 99%
See 1 more Smart Citation